Recent Study on Multi-objective Pareto Based Optimal Placement and Sizing of Solar PV and Wind Generation System - Giridhar, M. S.; Rani, P. Sobha (Advanced Aspects of Engineering Research Vol. 11, 2021)
To reduce power loss and improve the voltage profile of the power system, proper placement and sizing of distributed generation is needed. Solar photovoltaic (PV) and wind energy are two common distributed generation technologies. The authors present a novel multi-objective pareto-based approach for analysing the optimal positioning and sizing of solar PV and wind generation systems in a radial distribution system in this chapter. The built algorithm will be tested using a 33-bus distribution system. By placing a DG source at each bus and satisfying the objective function, the best location is detected. Here the maximum amount of Solar PV and Wind DG power injections for the distribution system considered have been identified considering the system constraints, beyond which it is technically as well as economically beneficial to pump the power to the grid. For optimum sizing of PV and wind systems, the Jaya algorithm is used. The system has also been analysed by installing the solar PV and wind generation systems separately and then together. The data is tabulated and visualised using three-dimensional plots.